Effect of Cropping Systems and Farming Systems to the Diversity of Insects on Potato Field in Karo Highland - Sidauruk, Lamria; Bakti, Darma; Kuswardani, Retna Astuti; Hanum, Chairani (Proceeding International Conference on Global Resource Conservation, 2015)
The spesies composition of arthropods on agro-ecosystem can be seen as a general indicator for ecosystem stability and ecological resilience. Agricultural intensification has been linked with losses of biodiversity and disruption of key ecosystem services in farmed landscapes. This study aimed to determine how cropping system and farming systems able to increase the diversity of insects on potato field, that can be used as an integrated pest management strategy. The result showed that insect diversity index and population of natural enemies in polyculture cropping system is higher than monoculture cropping system, while the pest population is lower. Insect diversity index and population of natural enemies in organic farming systems is higher than conventional farming systems, in general the pest population was lower in conventional farming systems, but not significant with organic farming system. The polyculture cropping potatoes+cabbage+mustard+celery, potatoes+cabbage, potato+mustard respectively which grown by organic farming systems provide the highest insect diversity index, the lowest percentage of crop damage, the lowest populations of pest, and the highest natural enemy populations when compared with the same polyculture cropping with conventional farming systems.Â Keywords: Cropping system; farming system; insect diversity; potato